Implementasi Pasal 131 Undang-Undang Nomor 17 Tahun 2023 dalam Progam Pemenuhan Gizi Perspektif Siyasah Tanfizdiyyah - Dhella Praviola (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Public nutritional fulfillment is a crucial aspect of improving health quality and human resource development. Article 131 of Law Number 17 of 2023 establishes the state’s responsibility in organizing nutritional fulfillment, including through free nutritious meal programs. This study employs a qualitative descriptiveanalytical approach to examine the implementation of this article in Gedong Tataan District through the Nutritional Fulfillment Service Unit. The results indicate that the program has increased public access to nutritious food but faces obstacles such as limited budgets, human resources, and inter-agency coordination. From the perspective of fiqh Siyasah Tanfidziyah, the program reflects the leader’s duty to ensure the welfare of the people (hifz al-nafs), while also highlighting the gap between legal norms (das sollen) and practical implementation (das sein), providing valuable lessons for the formulation of effective and sustainable nutrition policies.